The Irie Classroom Toolbox, a universal violence-prevention teacher-training programme, in Jamaican preschools: a single-blind, cluster-randomised controlled trial. Issue 4 (April 2021) - Baker-Henningham, Helen; Bowers, Marsha; Francis, Taja; Vera-Hernández, Marcos; Walker, Susan P
Summary: Background: Violence is a leading global public health problem, and interventions in early childhood are important in the primary prevention of violence. We tested whether the Irie Classroom Toolbox, a violence-prevention teacher-training programme reduced violence against children by teachers and reduced class-wide child aggression in Jamaican preschools (catering to children aged 3–6 years). Methods: We did a single-blind, cluster-randomised controlled trial in 76 preschools in Kingston and St Andrew, randomly selected, using simple randomisation, from 120 eligible preschools. Inclusion criteria were two to four classes of children; at least ten children per class; and located in an urban area. We randomly assigned preschools (1:1) to either the Irie Classroom Toolbox intervention or waiting-list control that received no intervention, using a computer-generated randomisation sequence by an independent statistician masked to school identity. The Toolbox involved training teachers in classroom behaviour management and promoting child social-emotional competence. All assessors were masked to group assignment. All teachers and classrooms in the selected schools participated in the study. Within each school, we used simple randomisation to randomly select up to 12 children aged 4 years for evaluation of child outcomes. The Toolbox intervention was implemented from August to April the following year. Teacher and classroom measures were done at baseline (the summer school term; ie, May to June), post-intervention (after 8 months of intervention; ie, May to June of the following year), and 1-year follow-up (ie, May to June 2 years later). The primary outcomes were observations of violence against children (including physical violence and psychological aggression) by teachers occurring across one full school day, and class-wide child aggression occurring over five 20-min intervals on another school day, all measured at post-intervention and 1-year follow-up and analysed by intention to treat. This trial is registered with ISRCTN, number ISRCTN11968472. Findings: Between June 22, 2015, and April 29, 2016, (after baseline measurements were completed), we assigned 38 preschools (with 119 teachers) to the Toolbox intervention and 38 preschools (with 110 teachers) to control. 441 children in the intervention schools and 424 in the control schools were included in the evaluation. All schools were included in the post-intervention and follow-up analyses. There were fewer counts of violence against children by teachers in the intervention schools compared with control schools at post-intervention (median counts 3 [IQR 0–11] vs 15 [3–35]; effect size −67·12%, 95% CI −80·71 to −53·52, p<0·0001) and 1-year follow-up (median counts 3 [IQR 0–9] vs 6 [1–16]; effect size −53·86, 95% CI −71·08 to −36·65, p<0·0001). No differences between groups were found for class-wide child aggression at post-intervention (effect size 0·07, 95% CI −0·16 to 0·29, p=0·72) or 1-year follow-up (−0·14, −0·42 to 0·16, p=0·72). Interpretation: In Jamaican preschools, the Irie Classroom Toolbox effectively reduced violence against children by teachers. The Toolbox was designed for use with undertrained teachers working in low-resource settings and should be effective with early childhood practitioners in other LMICs. Additional research is needed to further develop the Toolbox to reduce class-wide child aggression. Funding: Medical Research Council, Wellcome Trust, UK Aid, and the National Institute of Health Research.